PENTINGKAH ADVERSITY QUETIENT DALAM PENCAPAIAN PRESTASI AKADEMIK DI PERGURUAN TINGGI? - Efni Cerya (PAKAR Pendidikan, 2017)
The quality of education remains a central issue amidst the polemic of the education system in Indonesia. Educational goals that initially emphasize changes in behavior and mindset shift to value-oriented, graduation and even prestige. This has implications for graduates who are weak in self character, not ready to plunge into society and easily fragile to accept failure. Many individuals have high intelligence, but low in emotional and adversity quotient. For that, it is very important for students in improving and managing adversity quotient so that students will be more resilient in facing the problem and academic achievement.